Chemistry of Tertiary Carbon Center in the Formation of Congested C−O Ether Bonds. Issue 8 (22nd December 2020) - Hirata, Goki; Takeuchi, Kentarou; Shimoharai, Yusuke; Sumimoto, Michinori; Kaizawa, Hazuki; Nokami, Toshiki; Koike, Takashi; Abe, Manabu; Shirakawa, Eiji; Nishikata, Takashi
Abstract: Nucleophilic substitutions, including SN 1 and SN 2, are classical and reliable reactions, but a serious drawback is their intolerance for both bulky nucleophiles and chiral tertiary alkyl electrophiles for the synthesis of a chiral quaternary carbon center. An SRN 1 reaction via a radical species is another conventional method used to carry out substitution reactions of bulky nucleophiles and alkyl halides, but chiral tertiary alkyl electrophiles cannot be used. Therefore, a stereospecific nucleophilic substitution reaction using chiral tertiary alkyl electrophiles and bulky nucleophiles has not yet been well studied. In this paper, we describe the reaction of tertiary alkyl alcohols and non‐chiral or chiral α‐bromocarboxamides as a tertiary alkyl source for the formation of congested ether compounds possessing two different tertiary alkyl groups on the oxygen atom with stereoretention. Abstract : Cs2 CO3 reaction system enables stereospecific reaction of functionalized tertiary alkyl bromides and bulky alcohols. The reaction occurred with retention of configuration.